2019
DOI: 10.3365/kjmm.2019.57.3.154
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Alumina Dissolution from the Mechanically Activated Dross Using Ultrasound-Assisted Leaching

Abstract: Aluminum dross results from the re-melting of used aluminum cans, and is a valuable resource containing alumina. In general, aluminum dross contains oxides of Al, Ca, Fe, Mg, Si and Ti and some salts. As a continuation of the previous work to recover pure alumina from the dross, the effect of employing ultrasound wave in the NaOH solution was investigated to improve the leaching percentage of alumina from the mechanically activated dross. The use of ultrasound improved the leaching percentage of alumina from 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Ultrasound-assisted leaching technology has been extensively applied to extract valuable metals from metal ores, such as vanadium-bearing shale [16] , [19] , chalcopyrite [26] , [49] , scheelite [25] , [50] , [51] , zinc oxide ore [30] , [52] , [53] , nickel laterite ore [17] , rare earth ore [29] , refractory gold ore [27] , [54] , [55] , [56] , [57] , [58] , uranium ore [59] , [60] , K-feldspar [31] , copper-bearing biotite [43] , refractory silver ore [61] , eudialyte [62] , quartz sand [63] , [64] , [65] , [66] , [67] , [68] , poly-metallic sulfide ore [13] , deep-sea nodules [69] , phosphorus-potassium associated ore [21] , sphalerite [32] , and magmatic rocks [70] . In addition, ultrasound-assisted leaching has also been developed with successful enhancement in the leaching efficiency of metals from secondary resources, including metallurgical residues [3] , [15] , [35] , [38] , [39] , [42] , [48] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , spent catalysts [33] , [37] , …”
Section: Applications Of Ultrasound Technology In Metal Leaching Proc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound-assisted leaching technology has been extensively applied to extract valuable metals from metal ores, such as vanadium-bearing shale [16] , [19] , chalcopyrite [26] , [49] , scheelite [25] , [50] , [51] , zinc oxide ore [30] , [52] , [53] , nickel laterite ore [17] , rare earth ore [29] , refractory gold ore [27] , [54] , [55] , [56] , [57] , [58] , uranium ore [59] , [60] , K-feldspar [31] , copper-bearing biotite [43] , refractory silver ore [61] , eudialyte [62] , quartz sand [63] , [64] , [65] , [66] , [67] , [68] , poly-metallic sulfide ore [13] , deep-sea nodules [69] , phosphorus-potassium associated ore [21] , sphalerite [32] , and magmatic rocks [70] . In addition, ultrasound-assisted leaching has also been developed with successful enhancement in the leaching efficiency of metals from secondary resources, including metallurgical residues [3] , [15] , [35] , [38] , [39] , [42] , [48] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , spent catalysts [33] , [37] , …”
Section: Applications Of Ultrasound Technology In Metal Leaching Proc...mentioning
confidence: 99%
“…Li et al [137] reported that the leaching ratio of Al from quartz sand was increased from 12.22% to 42.25% with Na 2 CO 3 under ultrasound irradiation for only 25 min. Nguyen and Lee [79] also proposed the ultrasound-assisted NaOH leaching technique for the recovery of Al from aluminum dross, and it was obviously found that the leaching percentage of Al was improved from 35% to 60% with the use of ultrasound. In the meanwhile, researchers attempted to combine ultrasound with other processes to further improve the leaching recovery of Al.…”
Section: Applications Of Ultrasound Technology In Metal Leaching Proc...mentioning
confidence: 99%
“…Generally, the valuable metals in spent catalysts are recovered by leaching with either water after soda roasting or strong acid/base solutions 3,7,8) . The disadvantages of roasting followed by leaching are high consumption of energy 9) .…”
Section: Introductionmentioning
confidence: 99%